Que reste-t-il sur terre quand la sensibilité s’absente ? - Stéphane Collet (VertigO)
Instead of suffering from the contempory landscape orientation, that is mainly seekink for efficency, this essay is an atttempt to depict the various ways that affect the making off for the landscape, in a way that increase more and more its objet dimension instead of a sensitive approach. We will adopt a kind of methodology for breaking those issues. Our purpose will be to point out with a vade mecum a kind of jubilant landscape way of doing that let a place for invention and sensitive approach.